In Vivo Synthesis of Polyhydroxylated Compounds from a "Hidden Reservoir" of Toxic Aldehyde Species. Issue 15 (13th July 2017) - Bayer, Thomas; Milker, Sofia; Wiesinger, Thomas; Winkler, Margit; Mihovilovic, Marko D.; Rudroff, Florian
Abstract: Synthetic enzyme cascades in living cells often lack efficiency owing to the formation of byproducts by endogenous enzymes or toxicity of the cascade intermediates. Highly reactive aldehyde species can trigger a metabolic stress response, and this leads to undesired side reactions and decreased yields. Owing to the metabolic background of Escherichia coli ( E. coli ), aldehydes may be irreversibly oxidized to carboxylic acids or reduced to the corresponding alcohols. Herein, we applied an approach to equilibrate the aldehyde concentration in vivo. We oxidized primary alcohols to the corresponding aldehydes by AlkJ, an alcohol dehydrogenase from Pseudomonas putida . Introduction of a carboxylic acid reductase from Nocardia iowensis allowed the target compound to be retrieved from the carboxylate sink. Further reduction of the aldehydes to alcohols by endogenous E. coli enzymes completed the equilibration between alcohols, aldehydes, and carboxylic acids. Thus, the aldehyde concentrations remained below nonviable concentrations. We demonstrated the concept on several primary alcohols, which reached the redox equilibrium within 6 h and persisted up to 24 h. Subsequent combination with a dihydroxyacetone‐dependent aldolase (Fsa1‐A129S, E. coli ) demonstrated that the reactive aldehyde species were freely available and gave the aldol product, (3 S, 4 R )‐1, 3, 4‐trihydroxy‐5‐phenylpentan‐2‐one, in 70 % yield within short reaction times. Abstract : A biocatalytic funnel : The presented concept is a rational approach to tune the concentration of toxic aldehyde intermediates in living cells. We adjust the redox equilibrium between alcohol, aldehyde, and carboxylic acid species by combining an alcohol dehydrogenase with a carboxylic acid reductase to maintain the aldehyde concentration below the toxic levels, yet the reactive aldehyde species are freely available for subsequent aldolase‐mediated reaction.